Antioxidant potential and amino acid analysis of underutilized tropical fruit Limonia acidissima L. - Priya Darsini, Deivamarudhachalam Teepica; Maheshu, Vellingiri; Vishnupriya, Mounasamy; Nishaa, Surendran; Sasikumar, Jagathala Mahalingam (Free Radicals and Antioxidants)
Objective: Limonia acidissima L. an underutilized edible fruit was evaluated for its antioxidant activity, free radical scavenging ability, proximate and amino acid analysis using established in vitro assay models. Methods: 2,2-Diphenyl-1-picrylhydrazyl (DPPH ) radical scavenging assay, trolox equivalent antioxidant capacity (TEAC) assay, hydroxyl radical scavenging activity (HRSA), ferric reducing antioxidant power (FRAP) assay, nitric oxide radical (NO ) scavenging activity, total antioxidant activity (TAA) were carried out. The total phenolic (TP) and flavonoid contents (TF) of the extracts were determined and expressed as gallic acid and quercetin equivalents. Results: The highest percentage of phenol and flavonoid contents were observed in methanol and the lowest content was found in chloroform extract. Also, methanol extract recorded higher activity in DPPH , HRSA, FRAP and TAA whereas, ethyl acetate extract of the fruit was found to be active for ABTSþ radical scavenging activity. Further, water extract of the fruit exhibited potentially high nitric oxide radical scavenging activity than other solvent extracts. Moreover, the phenolic and flavonoid contents of the fruit extract significantly correlated with antioxidant capacity. Amino acid analysis revealed that among, all essential amino acids, the concentrations of isoleucine, phenylalanine and tryptophan were found to be present in higher amounts. Conclusion: Positive correlation was observed between polyphenolic contents and the antioxidant capacities. It is evident from the study that the fruit possess potent antioxidant activity with enormous health benefits and thus may be used in food and pharmaceutical applications.
Keywords: Tropical fruit; Limonia acidissima; Reducing power; Hydroxyl radical; Trolox equivalent